A política externa do governo FHC e a reinserção da economia brasileira na mundialização do capital (1995-2002) - Juvencio Sobrinho, Maria Goreti (2012)
This work is the result of an inquiry on the insertion of Brazil in global economy and on Brazilian foreign policy during Fernando Henrique Cardoso s administration (1995-2002). The research intends to show that in the context of ever intensifying capitalist globalization, under its influence and pressure, the colonial way of objectifying Brazilian capitalism is concluded. The process of implementation of industrial capitalism initiated in 1930 thus comes to an end. Throughout capitalist development, with its vicissitudes, conflicts, and struggles (which brought up different proposals aimed both at the full establishment of capitalism and the issue of social integration), Brazilian capitalism has actually consolidated as a subordinate and autocratic system. In its recent reinsertion in capitalist globalization through a broad restructuration of its productive apparatus, which reshaped some of its features, Brazilian capitalism accumulation and international subordination are still supported by labor force super-exploitation that tends in turn to be spread throughout capital system